Bringing pumps to people: giving the poor better access to groundwater irrigation: sustainable approaches and options for eastern India - International Water Management Institute (International Water Management Institute, 2002)
The State government has a vital role to play in developing groundwater resources to help improve the lot of the poorest people in eastern India's rural communities. Many States have tried to achieve this over the past 50 years through centrally planned public tube-well programs. Recently published research says that most of these efforts have failed to bring irrigation or improved livelihoods to the poor.